4-H Volunteer Training Series: The ABCs of 4-H: A Primer for 4-H Volunteers: 4H335, rev. 9/2024 - Dierenfield, Candi; Ghosh, Shreemoyee; Emerson, Jessica; Davis, Paula; Crawson, Nicole; Scarbrough, Bailea; Hafner, David (EDIS, 2024)
This information sheet is the introduction to the 4-H Volunteer Training Series (VTS). The series contains a wealth of information, from how to start a club, to planning field trips, to how to work with youth. This part was originally published in July 2014 and then revised in July 2018. It was updated in the summer of 2023 and is now revised in September 2024.